Cubic Polynomial

Algebra Level 5

Let p ( x ) p(x) and q ( x ) q(x) be two polynomials, both of which have their sum of coefficients equal to s > 0 s>0 . Let p p and q q satisfy p ( x ) 3 q ( x ) 3 = p ( x 3 ) q ( x 3 ) p(x)^3 - q(x)^3 = p(x^3) - q(x^3) .

Suppose that p ( x ) q ( x ) = ( x 1 ) 5 r ( x ) p(x) - q(x) = (x-1)^5 r(x) , where r ( x ) r(x) is a polynomial such that x 1 ∤ r ( x ) x-1 \not \mid r(x) . What is the value of s s ?


The answer is 9.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

James Pohadi
Apr 29, 2017

p ( x ) 3 q ( x ) 3 = p ( x 3 ) q ( x 3 ) ( p ( x ) q ( x ) ) ( p ( x ) 2 + p ( x ) q ( x ) + q ( x ) 2 ) = p ( x 3 ) q ( x 3 ) ( x 1 ) 5 r ( x ) ( p ( x ) 2 + p ( x ) q ( x ) + q ( x ) 2 ) = ( x 3 1 ) 5 r ( x 3 ) ( x 1 ) 5 r ( x ) ( p ( x ) 2 + p ( x ) q ( x ) + q ( x ) 2 ) = ( x 1 ) 5 ( x 2 + x + 1 ) 5 r ( x 3 ) r ( x ) ( p ( x ) 2 + p ( x ) q ( x ) + q ( x ) 2 ) = ( x 2 + x + 1 ) 5 r ( x 3 ) Putting x = 1 r ( 1 ) ( p ( 1 ) 2 + p ( 1 ) q ( 1 ) + q ( 1 ) 2 ) = ( 1 2 + 1 + 1 ) 5 r ( 1 3 ) r ( 1 ) ( s 2 + s 2 + s 2 ) = 3 5 r ( 1 ) 3 s 2 = 3 5 s 2 = 3 4 \begin{aligned} p(x)^3 - q(x)^3 &= p(x^3) - q(x^3) \\ (p(x) - q(x))( p(x)^{2} + p(x) q(x) + q(x)^{2} ) &= p(x^{3}) - q(x^{3}) \\ (x-1)^{5} r(x) ( p(x)^{2} + p(x) q(x) + q(x)^{2} ) &= (x^{3}-1)^{5} r(x^{3}) \\ (x-1)^{5} r(x) ( p(x)^{2} + p(x) q(x) + q(x)^{2} ) &= (x-1)^{5}(x^{2}+x+1)^{5}r(x^{3}) \\ r(x) ( p(x)^{2} + p(x) q(x) + q(x)^{2} ) &= (x^{2}+x+1)^{5}r(x^{3}) \\ \text {Putting } x=1 \implies r(1) ( p(1)^{2} + p(1) q(1) + q(1)^{2} ) &= (1^{2}+1+1)^{5}r(1^{3}) \\ r(1) ( s^{2}+s^{2}+s^{2} ) &= 3^{5} r(1) \\ 3s^{2} &= 3^{5} \\ s^{2} &= 3^{4} \end{aligned}

s = 9 s=\boxed{9} or s = 9 s=-9 (rejected since s < 0)

Note: p ( 1 ) p(1) and q ( 1 ) q(1) are the sum of the coefficients of p ( x ) p (x) and q ( x ) q (x) which is easy to prove.

Rajdeep Brahma
Mar 29, 2017

Part i is easy p ( 1 ) 3 q ( 1 ) 3 = p ( 1 ) q ( 1 ) . S o p ( 1 ) q ( 1 ) = 0. p(1)^3-q(1)^3=p(1)-q(1).So p(1)-q(1)=0.

So ( x 1 ) (x-1) divides p ( x ) q ( x ) p(x)-q(x) .Note s = p ( 1 ) = q ( 1 ) . ( p ( x ) q ( x ) ) ( p ( x ) 2 + p ( x ) q ( x ) + q ( x ) 2 ) = p ( x 3 ) q ( x 3 ) . s=p(1)=q(1). (p(x) - q(x)) ( p(x) ^2 + p(x) q(x) + q(x)^2 ) = p(x^3) - q(x^3).

So ( x 1 ) a r ( x ) ( p ( x ) 2 + p ( x ) q ( x ) + q ( x ) 2 ) = ( x 3 1 ) a r ( x 3 ) . (x - 1)^a r(x) ( p(x) ^2 + p(x) q(x) + q(x)^2 ) = (x^3 - 1)^{a} r(x^3) . Plug x = 1 x= 1 after cancelling (x-1)^a and we are done.

s 2 = 3 ( a 1 ) = 3 4 = 81. s^2=3^(a-1)=3^4=81. So s = 9. s=9.

Are you sure there are polynomials that satisfy the conditions of your question?

Calvin Lin Staff - 4 years, 2 months ago

Log in to reply

Why is there any contradiction???I do not know.Iwill let u know once I construct such a polynomial.

rajdeep brahma - 4 years, 2 months ago

Log in to reply

What you have shown is that if there are polynomials satisfying the conditions, then we must have s = 9 s = 9 . In order for the answer to not be meaningless, we have to demonstrate that there are such polynomials. Otherwise, any statement about the empty set is vacuously true.

In this case, because the condition is extremely restrictive, I'm concerned about the existence of such polynomials.

Calvin Lin Staff - 4 years, 2 months ago

s 2 = 81 s = ± 9 s^2 = 81 \Rightarrow s = \pm 9 and not only s = 9 s = 9 .!

Ankit Kumar Jain - 4 years, 2 months ago

Log in to reply

Thanks,I've edited it.

rajdeep brahma - 4 years, 2 months ago

Part i is easy p ( 1 ) 3 q ( 1 ) 3 = p ( 1 ) q ( 1 ) . S o p ( 1 ) q ( 1 ) = 0. p(1)^3-q(1)^3=p(1)-q(1).So p(1)-q(1)=0.

So ( x 1 ) (x-1) divides p ( x ) q ( x ) p(x)-q(x) .Note s = p ( 1 ) = q ( 1 ) . ( p ( x ) q ( x ) ) ( p ( x ) 2 + p ( x ) q ( x ) + q ( x ) 2 ) = p ( x 3 ) q ( x 3 ) . s=p(1)=q(1). (p(x) - q(x)) ( p(x) ^2 + p(x) q(x) + q(x)^2 ) = p(x^3) - q(x^3).

So ( x 1 ) a r ( x ) ( p ( x ) 2 + p ( x ) q ( x ) + q ( x ) 2 ) = ( x 3 1 ) a r ( x 3 ) . (x - 1)^a r(x) ( p(x) ^2 + p(x) q(x) + q(x)^2 ) = (x^3 - 1)^{a} r(x^3) . Plug x = 1 x= 1 after cancelling (x-1)^a and we are done.

s 2 = 3 ( a 1 ) = 3 4 = 81. s^2=3^(a-1)=3^4=81. So s = 9. s=9.

@rajdeep brahma , i just edited your solution using latex. You can copy and paste it if you want.

Hana Wehbi - 4 years, 1 month ago

Log in to reply

Thanks. I've pasted that in :)

Calvin Lin Staff - 4 years, 1 month ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...